Influence of Hf content on structure and electric properties of PHT thin films with self-buffered layer by PLD. (December 2016) - Li, Junfeng; Zhu, Jun; Wu, Zhipeng; Luo, Wenbo
Abstract: Three components of lead hafnate titanate (PbHfx Ti1–x O3, PHT) thin films have been fabricated by pulsed laser deposition (PLD) on the Pt (111)/Ti/SiO2 /Si (100) substrates. In order to reduce the mismatch between the thin films and substrates, low temperature self-buffered layer is adopted. The effects of Hf content on structure and electric properties of PHT thin films have been investigated. The PHT near the MPB (x = 0.48) shows the highest remnant polarization (2Pr = 93.23 μC/cm 2 ) and capacitance, even if its leakage current is a little worse than others. It should be noticed that the PHT ferroelectric films have a good performance after 2.15 × 10 10 fatigue reversals, which indicates that PHT films as a promising material can be applied in ferromagnetic random access memory (FRAM). Highlights: Owing to the difference of Hf content, three kinds of PHT films show different structures and electric performances. PbHf0.48 Ti0.52 O3 shows good electric performance due to the coexistence of two phases around MPB. PHT shows better fatigue performance than other ferroelectric films, which indicates PHT have a good prospect in FRAM.